2009 29th IEEE International Conference on Distributed Computing Systems Workshops 2009
DOI: 10.1109/icdcsw.2009.62
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Battery Model for Co-design in Cyber-Physical Systems

Abstract: We introduce a dynamic battery model that describes the variations of the capacity of a battery under time varying discharge current. This model supports a co-design approach for cyber-physical systems where control laws, online scheduling algorithms and battery management can be designed jointly to balance performance of the plant, the computing device, and the batteries. The input-output relationship of our model is equivalent to the Rakhmatov-Vrudhula-Wallach (RVW) model that has been verified by high fidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Battery-based power management: While battery management has been studied in the mobile/embedded domains [15,50,51] (e.g., drain rate adjustment for longevity), their use in datacenters has been limited to mere transition devices during utility failure. Recent work has looked at using UPS batteries to reduce electricity operational costs [20,44], but their role in tighter provisioning for reducing cap-ex is entirely novel.…”
Section: Related Workmentioning
confidence: 99%
“…Battery-based power management: While battery management has been studied in the mobile/embedded domains [15,50,51] (e.g., drain rate adjustment for longevity), their use in datacenters has been limited to mere transition devices during utility failure. Recent work has looked at using UPS batteries to reduce electricity operational costs [20,44], but their role in tighter provisioning for reducing cap-ex is entirely novel.…”
Section: Related Workmentioning
confidence: 99%
“…The power grid cyber-physical infrastructure is shown in Figure 9. Meanwhile, a dynamic battery model that supports control systems in CPS to enable the prediction of battery life was discussed in 2009 (Zhang et al, 2009). This is jointly done by an online scheduling algorithm and battery management framework to optimize the performance of the batteries, computing device and the plant as a whole.…”
Section: Electric Power Grid and Energy Systemsmentioning
confidence: 99%
“…In a survey of CPES [22], Macana et al identified the main research areas and challenges in energy systems. The authors in [23] proposed a dynamic battery model comprising different states representing discharge/recovery effects with scheduling algorithms. Yang [24] studied the application of IoT in a smart grid and highlights the main issues relating to large-scale IoT infrastructures in co-simulation platforms.…”
mentioning
confidence: 99%